American Colonialism in Puerto Rico: President Trump’s Response to Hurricane Maria - Martynuska, Małgorzata (Sensus Historiae, 2019)
The article is devoted to the commonwealth status of Puerto Rico which through its territorial annexation by the United States has become an “independent territory” controlled by the USA. It presents the treatment of Puerto Rico residents by President Trump’s administration in the context of Hurricane Maria. The paper is based on press articles published by The New York Times, USA Today, Huffington Post, El Nuevo Dia, and other newspapers that discuss the response of American government to the disaster caused by Hurricane Maria and compares it with the activities performed by President Trump in the cases of Texas after Hurricane Harvey and Florida after Hurricane Irma. Finally, the article links the inferior treatment of Hurricane Maria survivors with the ambiguous political status of Puerto Rico and raises the issue of American statehood as an option for consideration to solve the colonial status of the island.